THE NEED TO CREATE AN ALTERNATIVE ENERGY SYSTEM IN ELIMINATING ENVIRONMENTAL PROBLEMS (Multidisciplinary Journal of Science and Technology, 2024)
In this article, the information on the wide range of practical tasks carried out in the field of energy, the effectiveness of the use of alternative energy, the use of renewable sources, which is currently becoming the priority tasks of the state policy, is touched upon.